THE SCIENTIFIC RATIONALITY IN CONDITIONS OF THE INFORMATION SOCIETY - Ягодзінський, С. М. (Proceedings of the National Aviation University Series Philosophy Cultural, 2021)
There is hypothesis about the forming of the new style of thinking in the science of informational society. It was projected having the base of analysis of approaches to the classification of types of the scientific rationality and by means of mechanism of conversion from traditions to innovations in the scientific cognition. This process is connected with the using of the newest means of accumulation, treatment and transferring of information, which raise the question about advisability of probable, statistical and extrapolation methods in science.